Structurally dependent competing risks - Rosholm, Michael,Svarer, Michael (IZA, 2001)
In this paper, we specify and estimate a structurally dependent competing risks model for the transitions out of unemployment into either new job or recall. The recall probability is allowed to affect the search intensity for new jobs.
Keywords: Arbeitspapier; Graue Literatur; Arbeitslosigkeit; Dauer; Arbeitsuche; Mikroökonometrie; Schätzung; Theorie; Dänemark; Arbeitsmarktintegration